The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/scd.12071
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status of individuals with cerebral palsy at a nationally recognized rehabilitation center

Abstract: Cerebral palsy (CP) is a set of nonprogressive neuromuscular disorders caused by defects in the developing fetal brain. The aim of this study is to investigate the prevalence and distribution of various dental conditions including dental caries and periodontitis among individuals with CP who receive care at the Rancho Los Amigos National Rehabilitation Center dental clinic. Medical records of 478 patients between the ages of 3 and 78 years were reviewed. Patients were divided into four age groups: 3-20, 21-35,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…Various indices have been used to evaluate the periodontal status of children with motor and intellectual disabilities. It has been reported that the prevalence of gingivitis is relatively high in institutionalized children who receive adequate oral healthcare [22,34,37], and this is true for the children examined in the present study. Several factors contribute to the development of periodontal disease: hydantoin (which causes gingival hyperplasia), dry mouth, open bite, high viscosity of saliva, hypofunction of tongue movement, and difficulty in oral hygiene management [27,37].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Various indices have been used to evaluate the periodontal status of children with motor and intellectual disabilities. It has been reported that the prevalence of gingivitis is relatively high in institutionalized children who receive adequate oral healthcare [22,34,37], and this is true for the children examined in the present study. Several factors contribute to the development of periodontal disease: hydantoin (which causes gingival hyperplasia), dry mouth, open bite, high viscosity of saliva, hypofunction of tongue movement, and difficulty in oral hygiene management [27,37].…”
Section: Discussionsupporting
confidence: 61%
“…Dental caries is considered a common problem in children with neurological impairments [31], and some studies reported that the prevalence of dental caries in children with CP was similar to or lower than that in children in the general population [22,32]. The low caries rate in children with CP can be partly attributed to effective oral hygiene strategies for children with disabilities, including those with neurological impairments [33,34], although prevention of dental caries in patients with neurological impairments is still a major problem in some developing countries [35]. Patients with feeding tubes have been described as being at low risk for dental caries even with limited oral hygiene practice because they do not take food orally [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, oral health is a significant challenge, as individuals with CP are more prone to developing caries and periodontal disease, mouth-breathers and suffer from malocclusion, skeletal class II and anterior open bite. No intraoral anomalies are unique to persons with cerebral palsy but oral conditions are more severe than the general population [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the drugs used in the treatment of epilepsy and seizures may have a negative impact in the oral health [3]. These negative results are not common to all groups of patients with cerebral palsy and vary according to the region and the country in which the individual lives [1,4].…”
Section: Introductionmentioning
confidence: 99%